Ca(OH)2-mediated activation of peroxymonosulfate for the degradation of bisphenol S. Issue 53 (14th October 2021) - Wu, Leliang; Lin, Yiting; Zhang, Yimin; Wang, Peng; Ding, Mingjun; Nie, Minghua; Yan, Caixia; Chen, Shiyao
Abstract : Ca(OH)2 can activate PMS to effectively remove BPS, and it can meet the requirements of direct discharge after reaction. Abstract : Alkaline substances could activate peroxymonosulfate (PMS) for the removal of organic pollutants, but relatively high alkali consumption is generally required, which can cause too high pH of the solution after the reaction and lead to secondary pollution. Within this study, PMS activated by a relatively low dosage of Ca(OH)2 (1 mM) exhibited excellent efficiency in the removal of bisphenol S (BPS). The pH of the solution declined to almost neutral (pH = 8.2) during the reaction period and conformed to the direct emission standards (pH = 6–9). In a typical case, BPS was completely degraded within 240 min and followed the kinetics of pseudo-first-order. The degradation efficiency of BPS depended on the operating parameters, such as the Ca(OH)2, PMS and BPS dosages, initial solution pH, reaction temperature, co-existing anions, humic acid (HA), and water matrices. Quenching experiments were performed to verify that singlet oxygen ( 1 O2 ) and superoxide radicals (O2 ˙ − ) were the predominant ROS. Degradation of BPS has been significantly accelerated as the temperature increased. Furthermore, degradation of BPS could be maintained at a high level across a broad range of pH values (5.3–11.15). The SO4 −, NO3 − did not significantly impact the degradation of BPS, however, both HCO3 − and HA inhibited oxidation of BPS by the Ca(OH)2 /PMS system, and Cl − had a dual-edged sword effect on BPS degradation. In addition, based on the 4 identified intermediates, 3 pathways of BPS degradation were proposed. The degradation of BPS was lower in domestic wastewater compared to other naturals waters and ultrapure; nevertheless, up to 75.86%, 77.94% and 81.48% of BPS was degraded in domestic wastewater, Yaohu Lake water and Poyang Lake water, respectively. Finally, phenolic chemicals and antibiotics, including bisphenol A, norfloxacin, lomefloxacin hydrochloride, and sulfadiazine could also be efficiently removed via the Ca(OH)2 /PMS system.